Optimization of Mechanical Performance Polymer Insulators SiR Using CFA Waste as Filler - Miftahul Fikri; Iwa Garniwa Mulyana K; Christiono Christiono; Andi Amar Thahara (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2025)
This study investigates the use of coal fly ash as a filler in Room Temperature Vulcanization (RTV) silicone rubber to enhance its mechanical properties. Fly ash, which contains silica, has the potential to improve the strength of the polymer. The research aims to optimize the composition of fly ash in RTV silicone rubber composites using the quadratic regression method, focusing on tensile strength and elongation performance. Tests were conducted according to ASTM D 412 standards for tensile strength and elongation. The results showed that the optimal fly ash composition for tensile strength was 38.11%, resulting in a tensile strength of 0.19 and a Mean Absolute Percentage Error (MAPE) of 13.64%. For elongation, the optimal composition was 14.95%, with an elongation value of 192.094 and a MAPE of 24.75%. This study provides valuable insights into how fly ash can be used to enhance the mechanical properties of RTV silicone rubber composites.